The role of centralized reading of endoscopy in a randomized controlled trial of mesalamine for ulcerative colitis - Travis, S; Feagan, B; Sandborn, W; D'Haens, G; Pola, S; McDonald, J; Rutgeerts, P; Munkholm, P; Mittmann, U; King, D; Wong, C; Zou, G; et al. (Elsevier, 2013)
Background & Aims Interobserver differences in endoscopic assessments contribute to variations in rates of response to placebo in ulcerative colitis (UC) trials. We investigated whether centralized review of images could reduce these variations. Methods We performed a 10-week, randomized, double-blind, placebo-controlled study of 281 patients with mildly to moderately active UC, defined by an Ulcerative Colitis Disease Activity Index (UCDAI) sigmoidoscopy score ≥2, that evaluated the efficacy of delayed-release mesalamine (Asacol 800-mg tablet) 4.8 g/day. Endoscopic images were reviewed by a single expert central reader. The primary outcome was clinical remission (UCDAI, stool frequency and bleeding scores of 0, and no fecal urgency) at week 6. Results The primary outcome was achieved by 30.0% of patients treated with mesalamine and 20.6% of those given placebo, a difference of 9.4% (95% confidence interval [CI], −0.7% to 19.4%; P = .069). Significant differences in results from secondary analyses indicated the efficacy of mesalamine. Thirty-one percent of participants, all of whom had a UCDAI sigmoidoscopy score ≥2 as read by the site investigator, were considered ineligible by the central reader. After exclusion of these patients, the remission rates were 29.0% and 13.8% in the mesalamine and placebo groups, respectively (difference of 15%; 95% CI, 3.5%–26.0%; P = .011). Conclusions Although mesalamine 4.8 g/day was not statistically different from placebo for induction of remission in patients with mildly to moderately active UC, based on an intent-to-treat analysis, the totality of the data supports a benefit of treatment. Central review of endoscopic images is critical to the conduct of induction studies in UC; ClinicalTrials.gov Number, NCT01059344.